INFLUENCE OF AGING AND LIMB DOMINANCE ON REFERENCE VALUES OF MEDIAN AND ULNAR NERVE CONDUCTION STUDIES - Igor Sladojević; Tatjana Bućma; Milkica Glogovac Kosanović; Branislava Ćurčić (Биомедицинска истраживања, 2023)
Introduction: Median and ulnar nerves are mixed upper limb nerves. The aim of the research was to determine refer ence values, and influence of aging and limb dominance on electrophysiological parameters of these nerves. Methods: In 46 women and 14 men, aged 24 to 81, we de termined the conduction velocity (CV), the amplitude, and the distal motor latency (DML) on both nerves and their change with aging and limb dominance. In the group of women the influence of the postmenopausal period on the electrophysiological parameters of the median nerve was observed. Results: With aging, there was a significant decrease in the CV of sensitive fibers, amplitude of the motor part and DML of both nerves. In the median nerve, there was the decrease in the CV of motor fibers. On the dominant limb, there was the significant decrease in the CV of sensitive fibers of medi an nerve and amplitude of the sensitive part of ulnar nerve. On the dominant limb, aging caused the decrease of CV and the amplitude of the dorsal branch of the ulnar nerve, and CV of the motor fibers and DML of the median nerve. In postmenopausal women, the amplitude of the motor part of the median nerve decreased on the non-dominant limb. Conclusion: There is the influence of age and dominance on the electrophysiological parameters of the investigated nerves. The postmenopausal period in women, apart from the influence of aging, does not represent a specific influ encing factor on the investigated parameters.
Keywords: nerve conduction studies; normal values; hand